Rural Employment Problems in Ethiopia During the 1990s: A Critical Assessment (Indian Journal of Social Science and Literature (IJSSL), 2024)
This paper is derived from the author’s study on rural employment problems in Ethiopia. The research was conducted in 1998 in two rural districts of Ethiopia: Alemaya Woreda, eastern Hararghe and Shirka Woreda, Aresi zones. The study employed qualitative methods of data collection and qualitative techniques of analysis. This paper argues that unemployment and underemployment in Ethiopia, as elsewhere in Africa and least developed countries, are the major factors for the country’s underdevelopment. Yet unemployment or underemployment rarely, if any, receives attention from policy/decision makers. The paper examines the root causes of unemployment and the resulting poverty and underdevelopment of the country. A combination of historical, cultural, and political forces kept Ethiopia, speaking economically, a backward country, even though it chose to embrace Western values and ideals since the turn of the 20th century. The introduction of modern money, the establishment of banks, schools, hospitals, communication and service facilities brought the traditional society into direct and indirect contact, albeit with a considerable degree of selectivity and re-interpretation, to Europe and America at the height of their industrial development. One hundred years or so later, however, the Ethiopian society is still overwhelmingly rural, and to use the more value-loaded term, traditional. Therefore, it is underlined that the project of modernity could but marginalize the Ethiopian populace, and directly or indirectly contributed to the problem of rural employment in the country. The paper then outlines the underlying macro and micro-level causes and consequences of rural employment constraints since employment is massively rural in Ethiopia. The problem of unemployment impinges upon the welfare of the nation. The final section summarizes the paper and forwards some key recommendations that are believed to alleviate rural poverty and generate rural employment. Although the paper focuses on the realities of the 1990s, the lessons reflected, and the recommendations suggested are believed to be relevant to the present and the future.